Cooperation & collective action archaeological perspectives - Carballo, David M.; ebrary, Inc. (Boulder, Colo. : University Press of Colorado, 2013)
"Past archaeological literature on cooperation theory has emphasized competition's role in cultural evolution. As a result, bottom-up possibilities for group cooperation have been under-theorized in favor of models stressing top-down leadership, and evidence from a range of disciplines has demonstrated that humans effectively sustain cooperative undertakings through a number of social norms and institutions. Cooperation and Collective Action is the first volume to focus on the use of archaeological evidence to understand cooperation and collective action. Disentangling the motivations and institutions that foster group cooperation among competitive individuals remains a great conundrum in evolutionary theory. The breadth and material focus of archaeology provide a much-needed complement to existing research on cooperation and collective action, which thus far has relied largely on game-theoretic modeling, surveys of college students from affluent countries, brief ethnographic experiments, and limited historic cases. In Cooperation and Collective Action, diverse case studies address the evolution of the emergence of norms, institutions, and symbols in complex societies over the last 10,000 years. This book is an important contribution to the literature on cooperation in human societies and will appeal to archaeologists and other scholars interested in cooperation research"--
pt. I. Theoretical perspectives -- pt. II. Case studies.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Commerce, Prehistoric; Commerce, Prehistoric -- Cross-cultural studies; Economic anthropology; Economic anthropology -- Cross-cultural studies; Electronic books